Development of the Angioedema Control Test—A patient‐reported outcome measure that assesses disease control in patients with recurrent angioedema. Issue 5 (6th March 2020) - Weller, Karsten; Donoso, Tamara; Magerl, Markus; Aygören‐Pürsün, Emel; Staubach, Petra; Martinez‐Saguer, Inmaculada; Hawro, Tomasz; Altrichter, Sabine; Krause, Karoline; Siebenhaar, Frank; Metz, Martin; Zuberbier, Torsten; et al.
Abstract: Background: Recurrent angioedema (AE) is an important clinical problem in the context of chronic urticaria (mast cell mediator–induced), ACE‐inhibitor intake and hereditary angioedema (both bradykinin‐mediated). To help patients obtain control of their recurrent AE is a major treatment goal. However, a tool to assess control of recurrent AE is not yet available. This prompted us to develop such a tool, the Angioedema Control Test (AECT). Methods: After a conceptional framework was developed for the AECT, a list of potential AECT items was generated by a combined approach of patient interviews, literature review and expert input. Subsequent item reduction was based on impact analysis, inter‐item correlation, additional predefined criteria for item performance, and a review of the item selection process for content validity. Finally, an instruction section was generated, and an US‐American‐English version was developed by a structured translation process. Results: A 4‐item AECT with recall periods of 4 weeks and 3 months was developed based on 106 potential items tested in 97 patients with mast cell mediator‐induced (n = 49) or bradykinin‐mediated recurrent AE (n = 48). Eighty‐four items were excluded based on impact analysis. The remaining 22 items could be further reduced by a method‐mix of inter‐item correlation, additional predefined criteria for item performance and review for content validity. Conclusions: The AECT is the first tool to assess disease control in recurrent AE patients. Its retrospective approach, its brevity and its simple scoring make the AECT ideally suited for clinical practice and trials. Its validity and reliability need to be determined in future independent studies. Abstract : After a conceptional framework was developed for the AECT, 106 potentially relevant questions were identified during the item generation phase. The subsequent item reduction process, based on a combined approach of impact analysis and additional methods, selected a final set of 4 questions. The final 4‐item‐AECT is easy‐to‐administer, easy‐to‐complete, and easy‐to‐score which makes it ideally‐suited for clinical practice and trials. Abbreviation: AECT, angioedema control test